Email Issue for Working at Information Technology Field - Xavier, Idva Maria Das Dores Gomes (International Research Journal of Management, IT & Social Sciences, 2015)
The research was intended to know how matter of email function in working. Email has been used, when the first time everyone start to used internet. And email also the one of the social media that have in that time. Agree with the expansion of the internet, have a lot of people that use email to make a communication with the other people. One of the ways that make everyone happy to use email are easy to sending information and easy to use. Email afoot from optional communication to essential. This is proved if we see the work ethic in the big/great city. Every day and every time they canât stop to open their computer to check out their account email. Because they use to make a business communication from email. Once of the most popular application in the mobile devices is email client.